REKONSTRUKSI SEJARAH PENDIDIKAN ISLAM MASA BANI UMAYYAH: KAJIAN ATAS PERAN ULAMA DAN INSTITUSI ILMU - Almanar; Dewi, Eva; Sutarmo (JURNAL KAJIAN ISLAM MODERN, 2025)
This study reconstructs the history of Islamic education during the Umayyad Dynasty by highlighting the pivotal roles of scholars and early knowledge institutions in shaping the foundations of classical Islamic educational traditions. Employing a qualitative historical approach, the research draws upon primary sources such as Tarikh al-Ṭabari and Al-Bidayah wa al-Nihayah, complemented by contemporary academic literature. The findings reveal that scholars such as Hasan al-Basri and Ibn Shihab al-Zuhri served as teachers, jurists, and codifiers of hadith through halaqah-based learning, mosque circles, and scholarly travel (rihlah ilmiyyah). Educational institutions including mosques, scholarly circles, and early libraries played a crucial role in transmitting knowledge and developing networks of learning grounded in sanad. The curriculum centered on the Qur’an, hadith, fiqh, and the Arabic language, delivered through memorization, oral transmission, and dialogical methods. The study affirms that the Umayyad era laid an essential intellectual foundation for the more structured educational system that emerged under the Abbasid Caliphate and marked the initial phase of interaction between religious and rational sciences. Further comparative research is recommended to examine the intellectual continuity between the Umayyad and Abbasid periods.